2012
DOI: 10.1088/0953-2048/25/2/025016
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies on the magnetization of (RE)BCO bulk superconductors using various split-coil arrangements

Abstract: Simulation studies were conducted on the magnetization of (RE)BCO (RE–Ba–Cu–O, where RE represents a rare earth element) bulk superconductors using various split-coil arrangements by solving the critical state equation using the commercial software FlexPDE. A pair of coaxial coils of identical size is identified as an optimum arrangement for practical magnetization at 77 K by the ‘zero-field cooling’ technique. In general, the magnetization process is likely to be most effective when the outer radius of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Numerical simulation is a powerful tool to consider the obtained experimental results during PFM, and to understand the flux dynamics using electromagnetic and thermal equations. Several studies using the numerical simulation have been reported for PFM [17][18][19][20][21][22][23]. We have previously confirmed the advantage of the insertion of a soft iron yoke with a flat surface in the split coil numerically, and compared this to the case without the yoke [14,15].…”
Section: Introductionmentioning
confidence: 92%
“…Numerical simulation is a powerful tool to consider the obtained experimental results during PFM, and to understand the flux dynamics using electromagnetic and thermal equations. Several studies using the numerical simulation have been reported for PFM [17][18][19][20][21][22][23]. We have previously confirmed the advantage of the insertion of a soft iron yoke with a flat surface in the split coil numerically, and compared this to the case without the yoke [14,15].…”
Section: Introductionmentioning
confidence: 92%
“…The E-J power law (E α J n ) is used to simulate the non-linear electrical properties of the superconductors, where n = 21 and E 0 = 1 x 10 -4 V/m. J c0 is assumed to be 2 x 10 8 A/m 2 , which is consistent with the L measured material properties of the (RE)BCO bulk superconductors fabricated by the Cambridge Bulk Superconductivity Group [34].…”
Section: A Electromagnetic Modelmentioning
confidence: 84%
“…To analytically evaluate the relative rate of the magnetic relaxation within idealized Bean model applied to thick-walled cylinders, knowledge of the temperature distribution in the magnetization process is sufficient [7]. In the case of real annuli and particularly for the PFM [10], the calculation of shielding currents is quite difficult even under the isothermal magnetization [11]. In our work, the shielding current distribution was determined from the measurements of the axial magnetic field B z (r) in the gap between the annuli (at z = 0).…”
Section: Results Of Measurementsmentioning
confidence: 99%